2020
DOI: 10.1002/ctm2.118
|View full text |Cite
|
Sign up to set email alerts
|

Integrative clinical and molecular analysis of advanced biliary tract cancers on immune checkpoint blockade reveals potential markers of response

Abstract: Background While there have been encouraging preliminary clinical results for immune checkpoint inhibitors (ICIs) in BTCs, it remains a challenge to identify the subset of patients who may benefit. In this study, we evaluated the efficacy of ICI treatment in patients with advanced BTCs, and explored potential biomarkers that are predictive of response. Methods The study enrolled 26 patients with advanced microsatellite stable BTCs (15 with gallbladder cancers [GCs] and 11 with intrahepatic cholangiocarcinoma [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Consequently, the number of immunotherapy predictors described has been raising over the years, among which are included tumor mutation burden (TMB, a measurement of the number of mutations harbored by tumor cells), expression of immune checkpoint genes, microsatellite instability, and DNA mismatch repair defects [61,[116][117][118]. Recently, LRP1B mutation status was associated with improved patients' outcome to immunotherapy, being described as a biomarker for ICIs in multiple cancers such as melanoma, non-small cell lung cancer, prostate cancer, and advanced biliary tract cancer [58,79,89,119]. However, the exact mechanisms involved warrant further study.…”
Section: Lrp1b As a Therapeutic Target Prognostic Factor And Predictor Of Response To Therapymentioning
confidence: 99%
“…Consequently, the number of immunotherapy predictors described has been raising over the years, among which are included tumor mutation burden (TMB, a measurement of the number of mutations harbored by tumor cells), expression of immune checkpoint genes, microsatellite instability, and DNA mismatch repair defects [61,[116][117][118]. Recently, LRP1B mutation status was associated with improved patients' outcome to immunotherapy, being described as a biomarker for ICIs in multiple cancers such as melanoma, non-small cell lung cancer, prostate cancer, and advanced biliary tract cancer [58,79,89,119]. However, the exact mechanisms involved warrant further study.…”
Section: Lrp1b As a Therapeutic Target Prognostic Factor And Predictor Of Response To Therapymentioning
confidence: 99%
“…Out of 92 articles, 30 were excluded due to: no data for adenocarcinoma of the gallbladder available (N = 12), overlapping cohorts (N = 8), the wrong type of article (N = 5), no genetic alteration frequency data available (N = 3), wrong study population (N = 1), and not written in English (N = 1). A total of 62 articles were included for final data extraction, describing a total of 3893 GBC samples from individual patients [ 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that TMB-H is correlated with clinical response to immunotherapy in several tumors, including BTC, and that patients with TMB-H tumors can benefit from immune checkpoint inhibitors such as pembrolizumab [ 108 , 109 , 110 ]. In patients with GBC receiving immunotherapy, a higher objective response rate was observed for TMB-high tumors compared to TMB-low tumors (50% vs. 25%) [ 47 ]. Pembrolizumab has been FDA-approved for patients with TMB-H advanced solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with poor biological behavior could then be identified and treated with individual therapies [16]. In particular, LRP1B mutation was identified as a biomarker for ICIs in melanoma, non-small cell lung cancer [17], prostate cancer [18], and advanced biliary tract cancer [19].…”
Section: Ivyspringmentioning
confidence: 99%